Determinants of Financial Performance on Islamic Banks in ASEAN for Period 2019-2023 - Shelda Shelda; Fatih Fuadi; Ahmad Hazas Syarif (UIN Siber Syekh Nurjati Cirebon, 2025)
Islamic banks in ASEAN have a strategic role in supporting regional economic stability, but they also face various challenges in managing risks that can affect their financial performance. This study aims to analyze the determinants of the financial performance of Islamic banks in ASEAN, especially the influence of financing risk, liquidity risk, and capital adequacy on Return on Assets (ROA) as an indicator of financial performance. This study uses a purposive sampling method with a sample of five Islamic banks in ASEAN, namely Bank Muamalat Indonesia, Bank Islam Brunei Darussalam, Amanah Islamic Bank Philippines, Bank Islam Malaysia Berhad, and Bank Islamic Thailand, using annual data for the 2019-2023 period. The analysis was carried out with a panel data regression model using the EViews 10 program. The independent variables in this study include financing risk (NPF), liquidity risk (FDR), and capital adequacy (CAR). The results showed that partially, FDR had a significant negative influence on ROA with a value of Sig. 0.04 < 0.05, while NPF showed a positive significant influence with a value of Sig. 0.00 < 0.05. In contrast, CAR had no significant effect on ROA with a value of Sig. 0.5651 > 0.05. Simultaneously, FDR, NPF and CAR have a significant effect on the ROA of Islamic Banks in ASEAN for the 2019-2023 period.Keywords: Liquidity Risk (FDR), Financing Risk (NPF), Capital Adequacy (CAR), Financial Performance, Islamic Banks, ASEAN.